The golden ark: Arsenopyrite crystal plasticity and the retention of gold through high strain and metamorphism - Fougerouse, Denis; Micklethwaite, S.; Halfpenny, Angela; Reddy, Steven; Cliff, J.; Martin, L.; Kilburn, M.; Guagliardo, P.; Ulrich, S. (Blackwell Publishing Ltd, 2016)
Quantitative electron backscatter diffraction analysis and ion microprobe imaging of gold-rich arsenopyrites provide the first insights into the crystal plasticity and element mobility behaviour of arsenopyrites through metamorphism (340°-460° and 2 kbar). Remarkably, the gold-rich arsenopyrites remained structurally and chemically robust during high strain deformation. It was only during a superimposed lower strain deformation event, at a high angle to the preferred orientation of the arsenopyrites, that small amounts of crystal plasticity affected the arsenopyrites. During the low strain event, a dissolution-reprecipitation reaction resulted in loss of gold from the crystal lattice, facilitated by localised domains of recrystallisation, most likely due to fluid percolation along sub- and new grain boundaries. We suggest that the abundance and rheologically robust nature of gold-rich arsenopyrite in giant gold deposits, affected by greenschist-amphibolite metamorphism, is actually critical in the preservation of those deposits.